2004
DOI: 10.1073/pnas.0306622101
|View full text |Cite
|
Sign up to set email alerts
|

Copper-induced ferroportin-1 expression in J774 macrophages is associated with increased iron efflux

Abstract: Copper is known to play a role in iron recycling from macrophages. To examine whether cellular copper status affects expression of the iron exporter ferroportin-1 (FPN1), J774 macrophage cells were exposed to 10 -100 M CuSO4 for up to 20 h. Copper treatment significantly increased FPN1 mRNA in a dose-and time-dependent manner. After 20 h, 100 M CuSO4 up-regulated FPN1 transcript levels Ϸ13-fold compared to untreated controls. Induction was detected 8 h after copper treatment was initiated and markedly increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
8
33
1
1
Order By: Relevance
“…This suggests that there may be some pivotal interaction between the N terminus and the core of Slc11a proteins, such as occurs in the CPX-type copper-transporting P-type ATPases (68,69). Although there are no obvious ion-binding amino acids in the N terminus of Slc11a proteins, it was recently shown that deletion of the tyrosine-based Slc11a2-specific motif YSCF [62][63][64][65] inactivates transport function in mammalian cells but does not affect the subcellular localization (70). This motif is conserved in all mammalian Slc11a2, but not Slc11a1, homologues and might therefore play a role in determining symport function.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there may be some pivotal interaction between the N terminus and the core of Slc11a proteins, such as occurs in the CPX-type copper-transporting P-type ATPases (68,69). Although there are no obvious ion-binding amino acids in the N terminus of Slc11a proteins, it was recently shown that deletion of the tyrosine-based Slc11a2-specific motif YSCF [62][63][64][65] inactivates transport function in mammalian cells but does not affect the subcellular localization (70). This motif is conserved in all mammalian Slc11a2, but not Slc11a1, homologues and might therefore play a role in determining symport function.…”
Section: Discussionmentioning
confidence: 99%
“…5A, compare Lp02 to ΔmavN). As copper treatment has been linked to decreased intracellular iron stores, the ΔmavN-specific defect could be the result of copper aggravating the iron starvation experienced by the ΔmavN mutant (54).…”
Section: Resultsmentioning
confidence: 99%
“…Poor biologic availability may also be caused by an unfavorable oxidation state of the copper ion, which can be altered by macrophage-secreted molecules such as nitric oxide (37). Alternatively, minimization of copper stores in macrophages could represent a regulatory phenomenon, as copper has been shown to induce release of iron stores through a regulation of macrophage FPN1 expression (38). High expression levels of CTR4 were also exhibited by cryptococcal cells recovered from mouse brains, consistent with low levels of available copper in this organ.…”
Section: Discussionmentioning
confidence: 99%